Pengembangan Strategi Pemasaran Terhadap Produk Industri Rumah Tangga di Desa Sidoharjo Kecamatan Pulung - Robingatus Sa'diyah; Medina Nur Asyifa Purnama (Social Science Academic, 2023)
Most of the residents of Sidoharjo village work as home industry businesses. The problem that exists in these places is that they are only able to market their products in the surrounding environment. This is what makes the business very long and difficult to grow and become big. The purpose of this research is to create products that can be accepted by consumers in accordance with targeted marketing strategies and to develop businesses on a larger scale. The method used is Asset Based Community Development (ABCD). Implementation is carried out by providing assistance in marketing and promoting home industry business products. As for the results obtained from the assistance, which was initially only in the environment, now it has spread widely to other regions. So in conclusion, in training activities for developing a home industry marketing strategy is being able to understand insights about marketing strategies, have skills in marketing a home industry product and how to make products that are currently acceptable in the market so that products are able to compete in terms of quality and marketing.